Comparative Susceptibility of Channel Catfish, Ictalurus punctatus; Blue Catfish, Ictalurus furcatus; and Channel (♀) × Blue (♂) Hybrid Catfish to Edwardsiella piscicida, Edwardsiella tarda, and Edwardsiella anguillarum. Issue 1 (17th September 2017) - Reichley, Stephen R.; Ware, Cynthia; Khoo, Lester H.; Greenway, Terrence E.; Wise, David J.; Bosworth, Brian G.; Lawrence, Mark L.; Griffin, Matt J.
Abstract: Members of the genus Edwardsiella are important pathogens of cultured and wild fish globally. Recent investigations into the phenotypic and genotypic variation of Edwardsiella tarda have led to the segregation of E. tarda into three distinct taxa: E. tarda, Edwardsiella piscicida, and Edwardsiella anguillarum . In catfish aquaculture in the southeastern USA, E. piscicida has been more commonly associated with disease than E. tarda or E. anguillarum, and recent research has demonstrated E. piscicida to be more pathogenic in channel catfish than E. tarda or E. anguillarum . Anecdotal reports from industry suggest an increased prevalence of E. piscicida associated with the culture of channel (♀) × blue (♂) hybrid catfish. This work investigated the comparative susceptibility of channel catfish, blue catfish, and their hybrid cross to molecularly confirmed isolates of E. tarda, E. piscicida, and E. anguillarum . There was significantly higher mortality in hybrid catfish compared to channel catfish following intracoelomic injection of E. piscicida . To our knowledge, E. piscicida is the first bacterial pathogen to demonstrate increased pathogenicity in hybrid catfish compared to channel catfish.